Research on Noise Reduction in Industrial Buildings - Rashidov, Jasur Gayrat ugli; Azimova, Maftuna Shakarovna (European Journal of Life Safety and Stability (2660-9630), 2022)
This research paper, the effect of noise on the human body was studied, an analysis was made of the available methods and devices for attenuating noise in industrial buildings.